1981
DOI: 10.1128/jb.145.3.1317-1324.1981
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of distinct selenium-containing formate dehydrogenases from Escherichia coli

Abstract: Formate dehydrogenase, a component activity of two alternative electron transport pathways in anaerobic Escherichia coli, has been resolved as two distinguishable enzymes. One, which was induced with nitrate reductase as a component of the formate-nitrate reductase pathway, utilized phenazine methosulfate (PMS) in preference to benzyl viologen (BV) as an artificial electron acceptor and appeared to be exclusively membrane-bound. A second formate dehydrogenase, which was induced as a component of the formate hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Selenium labelling was performed as described by Cox et al (1981). Cells were grown aerobically for 8 h in TP medium (Heider et al, 1992) supplemented with 0.4% glycerol and 50 μg/ml cysteine.…”
Section: In Vivo Labelling With [ 75 Se]selenitementioning
confidence: 99%
“…Selenium labelling was performed as described by Cox et al (1981). Cells were grown aerobically for 8 h in TP medium (Heider et al, 1992) supplemented with 0.4% glycerol and 50 μg/ml cysteine.…”
Section: In Vivo Labelling With [ 75 Se]selenitementioning
confidence: 99%
“…Incorporation of the radioactive isotope [75Se] into FDHH and FDHN and their resolution on SDS-polyacrylamide gels were carried out as described by Cox et aL (1981).…”
Section: Incorporation Of [75se] Into Fdhsmentioning
confidence: 99%
“…Both FDH-1 and FDH-2 are selenoproteins (18) but differ in their molecular weights. Cox et al have observed that FDH-1 and FDH-2 had molecular weights of 110,000 and 80,000 respectively (8). The two enzymes also failed to cross-react immunologically (11).…”
Section: Materials and Methoqsmentioning
confidence: 99%